Spatio-temporal analysis of land use and land cover dynamics in a coastal South African metropolis and its implications for pedagogy and rural education - Olatoye, T. A.; Fru, R. N. (South African Journal of Higher Education, 2026)
This study investigates the spatio-temporal dynamics of land use and land cover (LULC) changes in the Buffalo City Metropolitan Municipality (BCMM), South Africa, and explores the implications of these changes for pedagogy and rural education. As the first of its kind in the study area, the research underscores the relevance of analysing ecological challenges and coastal vegetation conservation in the context of spatial development. The study collected data from advanced geo-spatial technologies, including satellite imagery and indices, spanning a 20-year period from 1998 to 2018. This comprehensive approach provides an in-depth overview of the extent and drivers of vegetation loss within the area. The analysis focused on establishing the relationship between LULC and two key indices: the Normalized Difference Vegetative Index (NDVI) and the Normalized Difference Built-Up Index (NDBI). LULC classification results were validated using five (5) different accuracy assessment techniques and tests. The results indicated a significant increase in built-up areas from 194 km² in 1998 to 814 km² in 2018, with statistical tests demonstrating high overall classification accuracies (R²=0.89 and P=0.86) over the study period. These results indicate that approximately 466 km² of forest vegetation has been lost in BCMM during the study period. The study’s findings have practical implications for policymakers, conservationists, educators, and rural communities, providing essential data and insights to inform policies and actions aimed at mitigating BCMM’s adverse environmental impacts and contributing to sustainable development.